Aphid infestation increases Fusarium langsethiae and T-2 and HT-2 mycotoxins in wheat - Drakulic, Jassy; Ajigboye, Olubukola; Swarup, Ranjan; Bruce, Toby; Ray, Rumiana V. (American Society for Microbiology., 2016)
Fusarium langsethiae is a fungal pathogen of cereal crops that is an increasing problem in northern Europe, but much of its epidemiology is poorly understood. The species produces the mycotoxins T-2 and HT-2, which are highly toxic. It was hypothesized that grain aphids, Sitobion avenae, may transmit F. langsethiae inoculum between wheat plants, and a series of transmission experiments and volatile chemical analyses was performed to test this. Manual translocation of aphids from inoculated to uninfected hosts resulted in pathogen DNA accumulation in hosts. However, the free movement of wingless aphids from infected to healthy plants did not. The addition of winged aphids reared on F. langsethiae-inoculated wheat seedlings to wheat plants also did not achieve successful pathogen transfer. While our data suggested that aphid transmission of the pathogen was not very efficient, we observed an increase in disease when aphids were present. After seedling inoculation, an increase in pathogen DNA accumulation in seedling leaves was observed upon treatment with aphids. Furthermore, the presence of aphids on wheat plants with F. langsethiae-inoculated ears not only led to a rise in the amount of F. langsethiae DNA in infected grain but also to an increase in the concentrations of T-2 and HT-2 toxins, with more than 3-fold higher toxin levels than diseased plants without aphids. This work highlights that aphids increase the susceptibility of wheat host plants to F. langsethiae and that aphid infestation is a risk factor for accumulating increased levels of T-2 and HT-2 in wheat products.